2015
DOI: 10.3389/fphys.2015.00331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Different Grip Angles on Physiological Parameters During Laboratory Handcycling Test in Able-Bodied Participants

Abstract: Introduction: Handcycling is a relatively new wheelchair sport that has gained increased popularity for people with lower limb disabilities. The aim of this study was to examine the effect of three different grip positions on physical parameters during handcycling in a laboratory setting.Methods: Twenty one able-bodied participants performed three maximum incremental handcycling tests until exhaustion, each with a different grip angle. The angle between the grip and the crank was randomly set at 90° (horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Currently, the only restriction imposed by the Union Cycliste Internationale (UCI) is that the crank height must be lower than the eye-line of the handcyclist [2]. Therefore, numerous areas of the handcycle-user interface can be manipulated, such as the backrest inclination [35], crank length [57] or handgrip orientation [7,8]. A recent qualitative study with expert handcyclists and coaches identified the horizontal displacement of the crank-axis with respect to the athlete, known as the crank fore-aft position, to be a key area of handcycle configuration with regards to performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only restriction imposed by the Union Cycliste Internationale (UCI) is that the crank height must be lower than the eye-line of the handcyclist [2]. Therefore, numerous areas of the handcycle-user interface can be manipulated, such as the backrest inclination [35], crank length [57] or handgrip orientation [7,8]. A recent qualitative study with expert handcyclists and coaches identified the horizontal displacement of the crank-axis with respect to the athlete, known as the crank fore-aft position, to be a key area of handcycle configuration with regards to performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, handcycling economy has frequently been reported to establish the physiological demand of a task. 26,35,47,52 Economy is calculated independent of the energy cost, whereby the submaximal VO 2 , at a given PO, can be used to define efficient performance. 96 Nonetheless, ME and economy are appropriate measures for within-subject experimental designs, if PO and cadence are controlled.…”
Section: Exercise Methodologiesmentioning
confidence: 99%
“…Only a limited number of reviewed studies have documented output parameters related to anaerobic performance during handcycling (Table 3; 114 athletes including 19 females). 26,35,47,[51][52][53][54][55] Further, while research exists concerning the anaerobic capabilities of athletes with a physical impairment during ACE, 56 no studies have recruited trained handcyclists. Of the studies shown in Table 3, only one recruited recumbent handcyclists with the rest studying AB participants, commonly in a touring configuration.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Few studies, however, have investigated the impact of the handbike-user interface or handbike design and construction on endurance performance. Research exploring the impact of the handbike-user interface on performance has focussed on the position and configuration of the cranks in ambulatory (Arnet et al 2014;Bafghi et al 2008;Faupin et al 2006; or recreational handcycling (Abel et al 2003(Abel et al , 2015Goosey-Tolfrey, Alfano, and Fowler 2008;Krämer, Hilker, and Böhm 2009;. Here, the configuration of the handbikes and demands on the participants differ considerably from elite handcycling thus, the influence that specific areas of racing handbike configuration have, on endurance performance, are unknown.…”
Section: Introductionmentioning
confidence: 99%